We will investigate how to solve " reduceable quadratic " equations.
A reduceable quadratic is a polynomial equation that is characterized by the following form:
![a\cdot x^(2n)\text{ + b}\cdot x^(2n-2)+c\text{ = d}](https://img.qammunity.org/2023/formulas/mathematics/college/pzzd3zextjjuyzf3cns18x7iwaipkmsxwo.png)
Where,
![a\text{ , b , c , d are constants}](https://img.qammunity.org/2023/formulas/mathematics/college/k22dumhgxtve137uvn8ybx3cb2cfvwkiz2.png)
And,
![n\text{ = 2}](https://img.qammunity.org/2023/formulas/mathematics/college/c28hndy2klagpsx2evq92du2sv84roex8v.png)
The equation given to us as follows:
![x^4-12x^2\text{ - 64 = 0}](https://img.qammunity.org/2023/formulas/mathematics/college/mvemmh0dm6xcoxtp3dl8impmgox9n4zkor.png)
We will follow a step-wise process in how to solve a reduceable quadratic once recognized.
Step 1: Reduce into a quadratic equation
In this step we will make an appropriate substitution using another variable such the given ( quartic ) equation is transformed into a ( quadractic ) equation as follows:
Substitution:-
![y=x^2](https://img.qammunity.org/2023/formulas/mathematics/college/1ch5n55tacdusoaz2xqjwppl7gqbo47w29.png)
Substitute the above variable into the given equation as follows:
![\begin{gathered} (y)^2\text{ -12}\cdot y\text{ - 64 = 0} \\ \textcolor{#FF7968}{y^2}\text{\textcolor{#FF7968}{ - 12y - 64 = 0}} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/agkxbhgl995veg3p6m5ricwua2ejqgegnl.png)
Step 2: Solve the reduced equation using quadratic formula
Now we will use the quadratic formula for finding roots. These roots are for the variable ( y ) NOT ( x ) as follows:
![y\text{ = }\frac{-b\pm\sqrt{b^2\text{ - 4ac}}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rckdptd0st83199gbgp9kuarfnj18de24l.png)
Where,
![\begin{gathered} ay^2\text{ + by + c = 0} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o3kqzz8vftlcqme5o7v8fm89kif3ugyi8t.png)
From the reduced quadratic we have:
![a\text{ = 1 , b = -12 , c = -64 }](https://img.qammunity.org/2023/formulas/mathematics/college/zyn06nbf32cncg5s0uh6se1rgknre4k4c4.png)
Plug in the constants into the quadratic formula and solve for roots for ( y ) as follows:
![\begin{gathered} y\text{ = }\frac{12\pm\sqrt{12^2\text{ - 4}\cdot1\cdot(-64)}}{2\cdot1} \\ \\ y\text{ = }\frac{12\pm\sqrt{144+\text{ 256}}}{2} \\ \\ y\text{ = }\frac{12\pm\text{ 20}}{2}\text{ = 6 }\pm\text{ 10} \\ \\ \textcolor{#FF7968}{y}\text{\textcolor{#FF7968}{ = 16 , -4}} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ptfdjajv2fpaupijwrb4l5odm72mcabob7.png)
We have solved for the two roots for the substitution variable ( y ) using the quadratic formula.
Step 3: Back substitution
We will back substitute the result of above variable ( y ) and solve for ( x ). Use the susbtitution made in the Step 1 as follows:
![\begin{gathered} y=x^2 \\ 16=x^2\to\text{ x = }\pm√(16)\text{ = }\pm4 \\ -4=x^2\to\text{ x = }\pm2i \\ \textcolor{#FF7968}{x}\text{\textcolor{#FF7968}{ = }}\textcolor{#FF7968}{\pm}\text{\textcolor{#FF7968}{ 4 , }}\textcolor{#FF7968}{\pm2i} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/42bb3t53rrlrs3ym8tik9gyb9i3130dpca.png)
Hence, the solutions to the given quartic equation is as follows:
![\textcolor{#FF7968}{x}\text{\textcolor{#FF7968}{ = }}\textcolor{#FF7968}{\pm}\text{\textcolor{#FF7968}{ 4}}\text{ AND}\text{\textcolor{#FF7968}{ x = }}\textcolor{#FF7968}{\pm2i}](https://img.qammunity.org/2023/formulas/mathematics/college/d1ib44d57qo7orwvioa935yd0w40ikfjxg.png)